Spotlight on the 9-valent HPV vaccine - Lopalco PL (Dove Medical Press, 2016)
Pier Luigi Lopalco Department of Translational Research and New Technologies in Medicine and Surgery, University of Pisa, Pisa, Italy Abstract: Starting in 2006, vaccination against human papillomavirus (HPV) has been progressively implemented in most developed countries. Two vaccines have been successfully used, a bivalent vaccine targeting HPV-related cancers (bHPV) and a quadrivalent vaccine (qHPV) targeting both HPV-related cancers and genital warts. Between December 2014 and June 2015, a new nonavalent HPV vaccine (9vHPV) was granted marketing authorization in the USA and Europe. The 9vHPV was developed from the qHPV and includes five additional HPV types that should increase the level of protection toward HPV-related cancers. Efficacy and/or immunogenicity of 9vHPV has been assessed in eight clinical studies. The 9vHPV vaccine induced a very robust immune response against all vaccine types, with seroconversion rates close to 100%. The safety profile of 9vHPV is comparable to that of qHPV. Local reactions, especially swelling, have been more frequently reported after 9vHPV than qHPV, and this slightly increases when the 9vHPV is coadministered with other vaccines. The additional coverage offered by the 9vHPV may prevent a significant proportion of HPV-related cancers (variable between 8% and 18%) depending on the local distribution of high-risk HPV types in the population. It is impossible, at present, to anticipate the actual impact of the wide use of the 9vHPV in comparison with the bHPV or the qHPV, since it depends on many variables including duration of protection, potential cross-protection toward nonvaccine types, and herd immunity effect. Keywords: human papillomavirus vaccine, immunogenicity, vaccine safety, cervical cancer, head and neck cancer, genital warts